Malawi Economic Monitor, May 2017 : Harnessing the Urban Economy - World Bank (World Bank, Lilongwe, Malawi, 2017)
The Malawi Economic Monitor (MEM) provides an analysis of economic and structural development issues in Malawi. This edition of the MEM was published in May 2017. It follows on from the four previous editions of the MEM, and is part of an ongoing series, with future editions to follow twice per year. The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavors to achieve high rates of stable, inclusive and sustainable economic growth. The MEM consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses in greater depth on a special, selected topic relevant to Malawi's development prospects.